Pengaruh Green Leadership terhadap Green Mindfulness pada Anggota Bank Sampah - Mutqi Sopiawadi; Reno Afriyadi Mayandika Pasha; Tri Nur Mujizat; Susi Wulandari; Panji Agnyoto (JABI (Journal of Accounting and Business Issues), 2024)
This study aims to determine the effect of green leadership on green mindfulness in members of the Bageur Waste Bank in Dangdeur Village, Subang Regency. The study used a survey method with a questionnaire to 30 respondents. The results of the validity and reliability tests showed that the data collection instrument was feasible to use. However, the results of regression analysis showed no real influence between green leadership and green mindfulness. Green leadership in Bank Sampah Bageur is carried out through environmental examples and education by its leaders, while members show an understanding of the importance of waste management. The limitations of the study are the small sample size and less than optimal communication between researchers and respondents. Further research with more comprehensive methods is recommended to understand the factors supporting green mindfulness in waste banks.